Toxicity of grasscutter (Thryonomys swinderianus temminck) faeces to Clarias gariepinus broodstock (2003)
This study investigates the performance of Clarias gariepinus broodstock fed with grasscutter faccal droppings. The physiological effects and growth performance of the fish were assessed after 8 weeks experimental feeding followed by 4 weeks of feeding with normal formulated (control) diet for fish. Ninety test fish were maintained solely on grasscutter faccal organic manure, while 30 fish maintained on the control diet served as the controls. The test fish suffered significant (p<0.05) weight loss compared to initial (pre-treatment) values and those of the control fish, but exhibited increased (p<0.05) growth within 4 weeks of being fed the control diet. They also developed normocytic, normochromic anaemia and lencocytosis characterized by lymphocytosis and heterophilia after 8 weeks of feeding. Analysis of the plasma metabolites of the test fish revealed hyponatracmia, hypochloraemia,acidosis, hypocreatininaemia, hypoproteinaemia, decreased enzyme activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Elevated plasma alkaline phosphatase (ALP) levels were observed, while the levels of plasma calcium phosphorous, area, potassium cholesterol, triglyceride,albumin,globulin and albumin globulin ratio remain unchanged throughout the experimental period. The haematologic and plasma biochemical changes in the test fish may be attributed to hepatorenal dysfunction, decreased protein metabolism, deficient protein content of grasscutter droppings and possibly associated with toxic materials in grasscutter faces. All the haematological and plasma biochemical changes in the test fish returned to normal 4 weeks after reversion to normal diet showing that grasscutter droppings are nutritionally sub-optimal and probably toxic to Clarias gariepinus broodstock and hence not recommended for total conventional feed replacement in C. gariepinus fish farming.